In vitro Cytotoxic Activity of New Triphenyltin (IV) Alkyl-isopropyl-di-thiocarbamate Compounds on Human Acute T-Lymphoblastic Cell Line - Normah Awang, Nor Syaidatul Akmal Mohd Yousof, Nor Fadilah Rajab, Nurul Farahana Kamaludin (Journal of Applied Pharmaceutical Science, 2015)
Cancer is one of the leading causes of mortality and morbidity worldwide. Various new metal-based compounds including organotin (IV) compounds have been actively synthesised due to their good cytotoxicity in cancerous cells. In this study, we tested the cytotoxicity of new triphenyltin (IV) dithiocarbamate compounds (triphenyltin (IV) benzylisopropyldithiocarbamate, compound 1; triphenyltin (IV) methylisopropyldithiocarbamate, compound 2; and triphenyltin (IV) ethylisopropyldithiocarbamate, compound 3) on the human acute T-lymphoblastic cell line, Jurkat E6.1 by MTT assay at three periods of time. The triphenyltin (IV) methylisopropyldithiocarbamate compound showed the lowest IC50 values (0.03 µM) after 24 h of treatment on Jurkat E6.1 cell lines. The IC50 values obtained for the three compounds for 24 h of treatment were 0.18 µM, 0.03 µM, and 0.42 µM, respectively. Next, for 48 h and 72 h of treatment, the IC50 values were 0.15 µM, 0.18 µM, and 0.40 µM and 0.18 µM, 0.19 µM, and 0.41 µM, respectively. These tested compounds were found to give cytotoxic activity against Jurkat E6.1 cell lines at micromolar doses. Observation on morphological changes of Jurkat E6.1 cell lines treated with IC50 values at 24 h of treatment showed morphological changes such as cell shrinkage and membrane blebbing, characterising the mode of cell death as apoptosis. Thus, further studies on the specific mechanisms of action of these compounds in human cells should be carried out to elucidate their potential as anticancer agents.
Keywords: Apoptosis,triphenyltin(IV),dithiocarbamate,MTT assay,cytotoxic.